Effect of water yam (Dioscorea alata) flour fortified with distillers spent grain on nutritional, chemical, and functional properties - Awoyale, W.; Maziya-Dixon, B.B.; Sanni, Lateef O.; Shittu, T.A. (Wiley, 2016)
It was envisaged that the inclusion of treated distiller ’ s spent grain ( DSG ) to yam fl our might increase its nutritional value, with the aim of reducing nutritional diseases in communities consuming yam as a staple. Hence, yam fl our was fortifi ed with DSG at 5–35%. The effects of this fortifi cation on the nutritional, chemical, and functional properties of yam fl our were investigated. The result showed a signifi cant increase ( P 0.001) in fat, ash, protein, total amino acids, total dietary fi ber, and insoluble dietary fi ber contents of the blends as DSG increased except for starch and soluble dietary fi ber contents, which decreased. The functional properties showed a signifi cant ( P 0.001) reduction with DSG inclusion. The inclusion of DSG increased both the tryptophan and methionine contents of the blends. Therefore, the DSG fortifi ed yam fl our could contribute to quality protein intake in populations consuming yam as a staple, due to its indispensible amino acid content.